Childhood neighborhood quality, friendship, and risk of depressive symptoms in adults: The China health and retirement longitudinal study - Chen, Haiyan; Xiong, Peng; Chen, Li; Hao, Guang (Journal of affective disorders, 2020)
•Childhood neighborhood quality was associated with the lower risk of depressive symptoms in adults.•Childhood friendship was associated with the lower risk of depressive symptoms in adults.•Higher education attainment enlarged the inverse associations between childhood neighborhood quality and depressive symptoms in adults.•Higher education attainment enlarged the inverse associations between childhood friendship quality and depressive symptoms in adults. Understanding the contribution of childhood neighborhood quality (CNQ) and childhood friendship (CF) to the development of depressive symptoms during adulthood among the general population is of great importance to public health. This study aims to examine the longitudinal associations of CNQ and CF with the risk of later-life depressive symptoms in a representative Chinese population. The data were from the China Health and Retirement Longitudinal Study (CHARLS). Depressive symptom score was measured by the 10-item Center for Epidemiological Studies-Depression Scale (CES-D10). CNQ and CF were measured by a standardized questionnaire. A total of 13,354 individuals were included in our study. The participants with higher CNQ had a significantly low risk of depressive symptoms than those with lower CNQ score (OR=0.93, 95%CI: 0.92–0.93, P<0.001), and the association remained significant (OR=0.93, 95%CI: 0.91–0.95, P<0.001) after further adjustment for covariates. The participants with a higher CF score had a significantly low risk of depresssive symptoms than those with a lower CF score (adjusted OR=0.97, 95%CI: 0.96–0.98, P<0.001). Moreover, the associations of CNQ and CF score with the risk of depressive symptoms were significantly modulated by education level (both P<0.001), which means that high education level enlarged the inverse associations of CNQ/CF with depressive symptoms. Higher CHQ and CF score are significantly associated with the lower risk of depressive symptoms in adulthood. Education attainment may mediate the associations of CNQ and CF with the risk of depressive symptoms.